2019
DOI: 10.9788/tp2019.4-15
|View full text |Cite
|
Sign up to set email alerts
|

Influence of roup Membership Moral alues and Belief in a ust orld in Blamin the ictim

Abstract: This study investigated the relationship between the victim's group membership and secondary victimization she suff ers, moderated by Moral Values and Belief in a Just World (BJW). The victim of the ingroup was blamed more for the sexual violence she suff ered (Study 1, N = 250). In turn, that relationship was moderated by binding values (Study 2, N = 117) and by BJW (Study 3, N = 258). Together, the results suggest that the victim blaming is greater when she belongs to the ingroup; and that this relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
2
0
2
Order By: Relevance
“…These results indicated that, in all the experimental conditions, men with high adherence to BJW blamed more than women did, and in the condition of black women, the level of blame was even higher. This result can be explained by the fact that women are judging victims from their own group (ingroup), as shown by several studies that analyze BJW in the context of intergroup relations (Albuquerque et al, 2019;Correia et al, 2015), showing that participants are more concerned with justice when confronted with victims from the ingroup than with victims from the outgroup.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These results indicated that, in all the experimental conditions, men with high adherence to BJW blamed more than women did, and in the condition of black women, the level of blame was even higher. This result can be explained by the fact that women are judging victims from their own group (ingroup), as shown by several studies that analyze BJW in the context of intergroup relations (Albuquerque et al, 2019;Correia et al, 2015), showing that participants are more concerned with justice when confronted with victims from the ingroup than with victims from the outgroup.…”
Section: Discussionmentioning
confidence: 97%
“…Research has shown that BJW is associated with legitimizing inequality between social groups and intensifies discriminatory behavior against blacks (da Costa Silva et al, 2018;Halabi et al, 2015). Similarly, various studies have shown that BJW is a strong predictor of blaming the victim of sexual violence (Albuquerque et al, 2019;Landström et al, 2016) and that men with high BJW tend to blame the victims more than women do (Strömwall et al, 2013). Despite these findings, we point out that no studies were found in the literature that analyzed the effect of the interaction between the victim's skin color, participant's gender, and their BJW, on blaming the victim of sexual violence.…”
Section: Studymentioning
confidence: 99%
“…O estudo de Albuquerque, Torres, Estramiana e Luque (2019) evidencia, então, que a alta adesão aos valores vinculativos produz uma maior vitimização secundária, independente de pertença grupal da vítima (variável psicossocial). Ademais, verificaram que a alta adesão aos valores vinculativos leva a uma maior culpa da vítima do grupo interno em comparação com a vítima do grupo externo (Albuquerque, Torres, Estramiana, & Luque, 2019). Assim, independente das características da vítima ou dela fazer parte ou não do grupo de quem a avalia (interno ou externo), ela é mais culpabilizada quando o avaliador adere a esses valores.…”
Section: Discriminação De Gênero E Sua Centralidade Na Compreensão Da...unclassified
“…Os resultados deste estudo apontam que a interação tripla entre a participação no grupo da vítima, a aderência aos valores vinculativos e a CMJ interferem no comportamento de culpar a vítima. A presença da vitimização secundária é evidente neste contexto, posto que a vítima sente-se culpada pela violência que sofreu, principalmente sob a influência de valores vinculativos e relacionados à CMJ (Albuquerque et al, 2019).…”
Section: A Teoria Do Mundo Justo E a Responsabilização Da Vítimaunclassified